Analysis of Rainfall as an Agroclimatological Element on Production and Determining the Planting Season of Corn (Zea Mays L.) in South Tapanuli Regency - Imelda Sari Harahap; Hery Solat (PT FORMOSA CENDEKIA GLOBAL, 2023)
Rain is a very important factor in the availability of water for planting. Farmers still use traditional methods in determining planting schedules. This determination is considered less than optimal. This research aims to analyze rainfall on corn production in South Tapanuli Regency based on rainfall data, and determine the relationship between rainfall and the suitability of sweet potato plants. The research method used is a survey method and literature review. This type of research is a survey method with a correlation and descriptive approach to see the relationship between rainfall and corn which is used using correlation. From this research, the results of correlation and regression analysis of rainfall variables on corn productivity variables over the last 10 years obtained from the South Tapanuli Regency Central Statistics Agency illustrate that the positive influence is weak.